Accounting System for Purchase of Raw Materials PT. Phillips Seafood Indonesia - Muhammad Dipa Taufikqurahman (PT. EQUATOR SINAR AKADEMIA, 2021)
The purpose of this study was to find out and obtain data regarding the Mandatory Employee Contribution (IWP) billing system for participants managed by PT. TASPEN (Persero) Serang Branch Office, as well as providing information to the participants of the pension program and Old Age Savings (ENT) how the process or flow goes through in collecting the Mandatory Employee Contribution (IWP) for these participants. The results of the study indicate that the Mandatory Employee Contribution (IWP) billing system for participants at PT. TASPEN (Persero) Serang Branch Office which has been created and implemented in the Company Operational Standards (SOP) has been explained in detail and has been implemented properly in accordance with the system created.